Analisis Pengaplikasian Medan Elektromagentik Terhadap Gelombang Radio Frekuensi Tinggi - Lutfi Apriyadi; Sabila Sofyana Zahra; Sabrina Nadya Octaviani; Diyajeng Luluk Karlina (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The electromagnetic field on high-frequency radio waves and its impact on signal transmission quality. High-frequency radio waves, used in wireless communication, can be affected by electromagnetic fields from various external sources, such as electronic equipment and building structures. This study analyzes the interaction between electromagnetic fields and radio waves, as well as their impact on transmission speed and signal range. The analysis results show that electromagnetic fields can cause distortion or interference in radio waves, affecting the quality of the received signal. This study provides deeper insights into the importance of managing electromagnetic fields to ensure stability and efficiency in high-frequency radio communication systems. The findings are expected to serve as a reference for the development of communication technology and the mitigation of electromagnetic interference on radio waves.